Zugeeignet - Riccabona, Christine,Ender, Marcus,Schneider, Ursula A.,Schorner, Michael,Steinsiek, Annette,Tanzer, Ulrike,Unterkircher, Anton,Wimmer, Erika,Zanol, Irene (Forschungsinst. Brenner-Archiv, 2020)
Vitrinenausstellung im Brenner-Archiv, Innsbruck, Oktober 2020 - März 2021; online: https://www.uibk.ac.at/brenner-archiv/neuerscheinungen/2020/zugeeignet.-widmungen-in-buechern-der-nachlassbibliotheken-des-brenner-archivs.html.
Keywords: Ausstellungskatalog